Uso didáctico de las tic y su incidencia en el rendimiento académico de los estudiantes de bachillerato de la unidad educativa “Carlos Lozada Quintana” del cantón La Maná, periodo lectivo 2021-2022. - Castillo Calva, Euclides Roberto (2023)
The Information and Communication Technologies "ICT" are all those programs, resources and tools used during synchronous and asynchronous classes, to carry out the exchange of information between the teacher and the student, becoming an essential contribution in the development of the teaching learning; The objective of this research is to analyze the use of ICT and its impact on the academic performance of students of the "Carlos Lozada Quintana" Educational Unit of the La Maná canton, in order to develop a methodological guide for didactic use. of ICT, which facilitates its use, encouraging and facilitating the integration of digital culture in the educational institution, with a sample of 7 teachers and 38 students to whom the instrument of directed surveys was applied for the diagnosis of the problem, to which was used, a methodology of qualitative-quantitative approach, qualitative because it allowed us to know the criteria of the students and the perception they have of the use of ICT by the teacher and quantitative in view of the fact that it gave us the opportunity to carry out an analysis statistics of the data obtained, with the different methods used during the investigation; With the results, it was possible to appreciate the level of knowledge and acceptance of the use of technological tools, which allowed the implementation of a methodological guide designed for the didactic use of ICT, in the teaching-learning process of high school students